Social inequality from symbolic domination in public and private institutions - Herrera Martell, Jessica; Herrera Caballero, Juan Manuel; Martell Martínez, Norma Georgina (Emerging Trends in Education, 2022)
One of the greatest challenges within the social sciences is to show the inequality that exists within educational organizations and institutions, which in this work will be analyzed from the interpretation of the microcosms (Habitus, Field, Capitals) of Pierre Bourdieu , which derive in a symbolic domination that is promoted in relation to the attached school to which the students belong, whether it is a public or private institution, as well as showing some of the elements that contribute to social inequality, through the mechanisms who collaborate in the reproduction of the same, derived from the capitals that individuals possess; The referential frameworks within the OS have left us a path in the conformation of the investigations within this field; Going back to Bourdieu in the study of organizations, not only implies carrying out the analysis of their categories, but also the understanding of these phenomena from a less functional sense, which focuses on the symbolic and the subjective, starting from the different rationalities of the OE, from a symbolic-interpretive approach, through the formation of capitals and in the conformation of field theory, to later show the reproduction of Bourdieu and Passeron. Keywords: Symbolic domination; education; inequality; social capital; subjetivity